Perancangan fasilitas kerja pada proses produksi batik kayu di sanggar peni krebet untuk meminimalisir Muscoloskeletal Disorders (MSDs) - Hisyammudin, Davis Achriyandi; Apsari, Ayudyah Eka (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
The wooden batik production process at Sanggar Peni Krebet supports the preservation of local culture and economy, but workers face the risk of musculoskeletal disorders due to unergonomic working positions. Based on the NBM questionnaire on 15 workers, the highest complaints occurred in the right upper arm (100%), right wrist (100%), and waist (88%). Analysis with the RULA and REBA methods showed that the batik activity is very high risk (RULA 7, REBA 11), requiring immediate improvement, while boiling has moderate to high risk (RULA 5, REBA 9), requiring investigation. Ergonomics Facility Design (EFD) recommends redesigning the boiling stove, chair, and table to suit body posture, ergonomic working position, and a strainer with comfort grip. The tool design should improve comfort, safety, and efficiency, using lightweight and strong materials. This implementation is expected to improve safety and productivity in the batik industry.